1998
DOI: 10.1016/s0960-9822(98)70277-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of the ezrin-binding site in the hyaluronan receptor, CD44

Abstract: ERM (ezrin, radixin and moesin) proteins function as linkers between the actin cytoskeleton and the plasma membrane. In addition to this structural role, these proteins are highly regulatable making them ideal candidates to mediate important physiological events such as adhesion and membrane morphology and to control formation and breakdown of membrane-cytoskeletal junctions. Recently, a direct interaction in vitro has been demonstrated between ERM proteins and the hyaluronan receptor, CD44. We have mapped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 29 publications
(22 reference statements)
3
148
0
2
Order By: Relevance
“…This raises the question of whether these proteins might be interacting at the looped structure. It has been reported that ezrin links the cytoplasmic domain of CD44 to the actin cytoskeleton in baby hamster kidney cells and mouse L ®broblasts (Tsukita et al, 1994;Yonemura et al, 1998Yonemura et al, , 1999Legg and Isacke, 1998), but we do not know if this interaction occurs in FBR cells. None of our data allow us to conclude that Krp1 interacts with these proteins, but the presence of all of them at pseudopod tips upon transformation of 208F cells supports the hypothesis that AP-1 regulates the expression of these genes, and that they are recruited to a structure that is likely to allow transformed cells to become invasive (Guirguis et al, 1987;Hay, 1989;Lamb et al, 1997b;Liotta et al, 1991b;Nabi et al, 1999).…”
Section: Discussionmentioning
confidence: 77%
“…This raises the question of whether these proteins might be interacting at the looped structure. It has been reported that ezrin links the cytoplasmic domain of CD44 to the actin cytoskeleton in baby hamster kidney cells and mouse L ®broblasts (Tsukita et al, 1994;Yonemura et al, 1998Yonemura et al, , 1999Legg and Isacke, 1998), but we do not know if this interaction occurs in FBR cells. None of our data allow us to conclude that Krp1 interacts with these proteins, but the presence of all of them at pseudopod tips upon transformation of 208F cells supports the hypothesis that AP-1 regulates the expression of these genes, and that they are recruited to a structure that is likely to allow transformed cells to become invasive (Guirguis et al, 1987;Hay, 1989;Lamb et al, 1997b;Liotta et al, 1991b;Nabi et al, 1999).…”
Section: Discussionmentioning
confidence: 77%
“…A striking feature of 507 RKIKK 511 residues is the presence of positively charged amino acids. A positively charged amino acid cluster in the juxta-membrane portion has been identified as an ERM protein-binding region in CD43, CD44, and ICAM-2 (Legg and Isacke, 1998;Yonemura et al, 1998). Therefore, instead of binding to ␣-actinin, this motif may also serve as a binding site for ERM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell, approximately 75% of PKA is associated with AKAPs (Sim and Scott, 1999). A candidate AKAP in the phosphorylation of CD44 is ezrin (Dransfield et al, 1997), a member of the ERM family of proteins that interact with CD44 at a membrane proximal site in the CD44 cytoplasmic tail (Legg and Isacke, 1998;Yonemura et al, 1998). Alternatively, the four terminal amino acids (Lys-IleGly-Val) correspond to a consensus postsynaptic density protein/discs-large protein/zonula occludens-1 (PDZ) domain binding motif (Thorne et al, 2004).…”
Section: Discussionmentioning
confidence: 99%